A conserved loop structure of GH19 chitinases assists the enzyme function from behind the core-functional region. (22nd November 2021) - Kawamoto, Daiki; Takashima, Tomoya; Fukamizo, Tamo; Numata, Tomoyuki; Ohnuma, Takayuki
Abstract: Plant GH19 chitinases have several loop structures, which may define their enzymatic properties. Among these loops, the longest loop, Loop-III, is most frequently conserved in GH19 enzymes. A GH19 chitinase from the moss Bryum coronatum (BcChi-A) has only one loop structure, Loop-III, which is connected to the catalytically important β-sheet region. Here, we produced and characterized a Loop-III-deleted mutant of BcChi-A (BcChi-A-ΔIII) and found that its stability and chitinase activity were strongly reduced. The deletion of Loop-III also moderately affected the chitooligosaccharide binding ability as well as the binding mode to the substrate-binding groove. The crystal structure of an inactive mutant of BcChi-A-ΔIII was successfully solved, revealing that the remaining polypeptide chain has an almost identical fold to that of the original protein. Loop-III is not necessarily essential for the folding of the enzyme protein. However, closer examination of the crystal structure revealed that the deletion of Loop-III altered the arrangement of the catalytic triad, Glu61, Glu70 and Ser102, and the orientation of the Trp103 side chain, which is important for sugar residue binding. We concluded that Loop-III is not directly involved in the enzymatic activity but assists the enzyme function by stabilizing the conformation of the β-sheet region and the adjacent substrate-binding platform from behind the core-functional regions.